Analysis of Zila Panchayat Finances of Bareilly Division - Singh, Dr. Bhupender (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
India has been a welfare state ever since its independence and the primary objective of all governmental endeavors has been the welfare of its people. Elimination of poverty, ignorance, diseases and inequality of opportunities and providing a better and higher quality of life were the basic premises upon which all the plans and blue-prints of development were built. According to Ministry of Rural Development (Govt. of India), rural development implies both the economic betterment of people as well as greater social transformation. Development of rural areas has been at the core of planning process in the country and also in the States. Rural Development is a broad, inclusive term which takes into consideration socio-economic and political development of the rural areas. It includes measures to strengthen the democratic structure of the society through the Panchayati Raj Institutions as well as measures to improve the rural infrastructure, income of rural households and delivery systems pertaining to education, health and safety mechanisms. Poverty alleviation is a key component of rural development. Government of India has taken many initiatives for rural development and the strengthening the Panchayati Raj Institutions is one of the important steps taken by the Central Government. Key words- Panchayati, Resources, Finance, Income, Expenditure, Development